Pengaruh Kepemimpinan Autentik Kepala Sekolah Dan Iklim Sekolah Terhadap Komitmen Guru Pada SD Negeri Di Kecamatan Padang Jaya Bengkulu Utara - Arpen Fitrawilan (Manajer Pendididikan, 2023)
This study aims to analyze the influence of the authentic leadership of the school principal and school climate on teacher commitment to public elementary schools in Padang Jaya District, North Bengkulu Regency. The approach used in this research is descriptive quantitative. Data collection techniques in this study used a questionnaire instrument. This study used a sample of 160 people from elementary school teachers in Padang Jaya District, North Bengkulu. The sampling technique used in this study was purposive cluster random sampling. Calculation analysis in this study to determine the hypothesis using the help of the SPSS version 22 application for windows. The conclusion from this study is that simultaneously authentic leadership and school climate together influence the commitment of teachers in schools. Partially, each variable (authentic leadership and school climate) significantly influences the commitment of elementary school teachers in Padang Jaya District, North Bengkulu